2021
DOI: 10.3389/fimmu.2021.639818
|View full text |Cite
|
Sign up to set email alerts
|

The CD28-Transmembrane Domain Mediates Chimeric Antigen Receptor Heterodimerization With CD28

Abstract: Anti-CD19 chimeric antigen receptor (CD19-CAR)-engineered T cells are approved therapeutics for malignancies. The impact of the hinge domain (HD) and the transmembrane domain (TMD) between the extracellular antigen-targeting CARs and the intracellular signaling modalities of CARs has not been systemically studied. In this study, a series of 19-CARs differing only by their HD (CD8, CD28, or IgG4) and TMD (CD8 or CD28) was generated. CARs containing a CD28-TMD, but not a CD8-TMD, formed heterodimers with the end… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…A previous study has shown that site-specific integration of a CD19-CAR into the TCR alpha constant region ( TRAC ) of T cells results in a more uniform distribution and TCR-like regulation of CAR surface expression, thereby mitigating T-cell exhaustion and enhancing anti-tumor activity ( 21 ). In addition, we recently observed that CAR hi human T effector cells exhibited a surprisingly robust proliferative response to anti-CD28 stimulation alone, independent of CAR or TCR engagement, whereas CAR lo T effector cells did not ( 22 ). Thus, lentivirally engineered Tregs may result in heterogeneous CAR expression and unexpected properties of the engineered cells.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that site-specific integration of a CD19-CAR into the TCR alpha constant region ( TRAC ) of T cells results in a more uniform distribution and TCR-like regulation of CAR surface expression, thereby mitigating T-cell exhaustion and enhancing anti-tumor activity ( 21 ). In addition, we recently observed that CAR hi human T effector cells exhibited a surprisingly robust proliferative response to anti-CD28 stimulation alone, independent of CAR or TCR engagement, whereas CAR lo T effector cells did not ( 22 ). Thus, lentivirally engineered Tregs may result in heterogeneous CAR expression and unexpected properties of the engineered cells.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that site-specific integration of a CD19-CAR into the TCR alpha constant region ( TRAC ) of T cells results in a more uniform distribution and TCR-like regulation of CAR surface expression, thereby mitigating T-cell exhaustion and enhancing anti-tumor activity (13). In addition, we recently observed that CAR hi human T cells exhibited a surprisingly robust proliferative response to anti-CD28 stimulation alone, independent of CAR or TCR engagement, whereas CAR lo T cells did not (14). Thus, lentivirally engineered Tregs may result in heterogeneous CAR expression and unexpected properties of the engineered cells.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal Mackall and co-workers demonstrated that swapping the CD8-TMD/HD in a CD19 4-1BB-ζ CAR for a CD28-TMD-HD lowered the antigen density threshold for CAR T-cell activation ( 14 ). Finally, we have recently demonstrated that CD28 TMD-containing CARs can recruit and dimerize with endogenous CD28, which normally exists as a homodimer on the cell surface, via a four amino acid motif in the TMD ( 15 , 16 ). Consistent with this, in-depth analysis of the CAR interactome and signalosome revealed that the top interacting partner of a CAR bearing a CD28-TMD/HD is endogenous CD28, and CAR mediated-signaling is associated with phosphorylation of endogenous CD28 ( 9 , 17 ).…”
Section: The Impact Of the Car Transmembrane Domain In Car T-cell Toxicitymentioning
confidence: 99%
“…Consistent with this, in-depth analysis of the CAR interactome and signalosome revealed that the top interacting partner of a CAR bearing a CD28-TMD/HD is endogenous CD28, and CAR mediated-signaling is associated with phosphorylation of endogenous CD28 ( 9 , 17 ). This association, through heterodimerization of the CAR with endogenous CD28 receptor via the CD28-TMD ( 15 ), may result in stronger signal transduction, facilitating CAR T-cell activation in the context of low levels of CAR antigen, such as in low-CD19 mural cells. It is interesting to note that CD28-CAR heterodimerizes inefficiently if the CAR is built with an IgG4-HD.…”
Section: The Impact Of the Car Transmembrane Domain In Car T-cell Toxicitymentioning
confidence: 99%
See 1 more Smart Citation